HUKUM ADAT SEBAGAI PRANATA HUKUM PENYELESAIAN PERSELISIHAN MELALUI MUSYAWARAH MUFAKAT DALAM LINGKUNGAN MASYARAKAT - Gindo L. Tobing (Fakultas Hukum Universitas Kristen Indonesia, 2016)
In daily life by people in Indonesia the use of the term customs with customary law is often equated. It is as if the two terms have the same meaning and meaning or even people say custom. Custom or habit is always connoted as a reflection of the life of a particular society, a society that has not known progress, or society that is still old, traditional, not familiar with modernization. Habits can be seen for example from behavior, speech, politeness that can describe the characteristics of a society. With the advancing civilization of society which is driven by economic development, science and technology, the level of conflict or dispute in society is also higher. Settlement of disputes or conflicts should not always be resolved through formal legal channels eg through a complaint to law enforcement officers (police) or filing a lawsuit through courts but can also be resolved through consensus or peace agreement using customary law (including local wisdom). When customary law plays its role at that time the public will realize that modernization does not forever necessarily leave and even eliminate the role of customary law. Customary law is also capable of resolving the various conflicts that arise in society. Keywords: Customary law as legal institution to solve various conflicts in society